2001
DOI: 10.1080/00039890109604056
|View full text |Cite
|
Sign up to set email alerts
|

Lung Mineral Fibers of Former Miners and Millers from Thetford-Mines and Asbestos Regions: A Comparative Study of Fiber Concentration and Dimension

Abstract: Fiber dimension and concentration may vary substantially between two necropsy populations of former chrysotile miners and millers of Thetford-Mines and Asbestos regions. This possibility could explain, at least in part, the higher incidence of respiratory diseases among workers from Thetford-Mines than among workers from the Asbestos region. The authors used a transmission electron microscope, equipped with an x-ray energy-dispersive spectrometer, to analyze lung mineral fibers of 86 subjects from the two mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The exposures to the "noncommercial" forms of asbestos may be due to their presence as mixtures in products made from other minerals. For example, it has been reported that some chrysotile is "contaminated" with amphiboles (McDonald & McDonald, 1997;McDonald et al, 1989;Churg, 1988;Churg et al, 1993;Sebastien et al, 1989;Nayebzadeh et al, 2001). It has also become increasingly evident to health scientists, as mineralogists have long recognized, that types of asbestos can be found in mineral deposits that are mined for various products often construed to be asbestos free Dodson & Levin, 2001;DeVuyst et al, 1987;McDonald et al, 1986).…”
Section: Discussionmentioning
confidence: 93%
“…The exposures to the "noncommercial" forms of asbestos may be due to their presence as mixtures in products made from other minerals. For example, it has been reported that some chrysotile is "contaminated" with amphiboles (McDonald & McDonald, 1997;McDonald et al, 1989;Churg, 1988;Churg et al, 1993;Sebastien et al, 1989;Nayebzadeh et al, 2001). It has also become increasingly evident to health scientists, as mineralogists have long recognized, that types of asbestos can be found in mineral deposits that are mined for various products often construed to be asbestos free Dodson & Levin, 2001;DeVuyst et al, 1987;McDonald et al, 1986).…”
Section: Discussionmentioning
confidence: 93%
“…Only two of the seven ATSDR panelists felt there was a reasonable certainty of no harm from short fibers while the other five remained concerned about the ability of short fibers to cause harm [ATSDR, 2003]. In fact, tremolite asbestos fibers were found to produce the highest average fibrosis grades when exposures were to average tremolite fibers less than 5 mm in length [Nayebzadeh et al, 2001].…”
Section: Toxicity Of Short Asbestos Fibersmentioning
confidence: 97%
“…The gradation of the diameter of the bare fibers and central fibers of asbestosic bodies according to the type of asbestos mainly follows the following trend: chrysotile < crocidolite < amosite < tremolite < anthophyllite. The diameter, however, tends to increase with the length of the fibers (Case and Dufresne, 1997;Case et al, 2000;Nayebzadeh et al, 2001) Long asbestos fibers, and in particular amphibole fibers, are found in the lungs of cases exposed through activities principally based on SAFs, such as servicing brake pads, which are known to only contain chrysotile (Finley et al, 2007).…”
Section: Toxicokinetics-metabolism Of Safs and Tafsmentioning
confidence: 98%